Synergistic enhancement and mechanism study of mechanical and moisture stability of perovskite solar cells introducing polyethylene-imine into the CH3NH3PbI3/HTM interface. Issue 44 (2nd October 2015) - Yun, Jae Hoon; Lee, Inhwa; Kim, Taek-Soo; Ko, Min Jae; Kim, Jin Young; Son, Hae Jung
Abstract : Introduction of polyethyleneimine (PEI) onto the perovskite layer allows HTMs to strongly adhere to the perovskite layer, simultaneously enhancing moisture stability. Abstract : High performance perovskite solar cells with high stability in moist air are required for their practical applications. We have developed a simple approach to enhance device stability via the introduction of a polyethyleneimine (PEI) compatibilizer between the perovskite (CH3 NH3 PbI3 ) and upper hole transporting material layers (HTMs). The PEI effectively reduces moisture intrusion into the CH3 NH3 PbI3 layer under a high humidity condition. Moreover, the incorporation of PEI increases the adhesion at the CH3 NH3 PbI3 /HTM interface, which allows the protective HTMs to strongly adhere onto the CH3 NH3 PbI3 layer during degradation and significantly decreases the direct exposure of CH3 NH3 PbI3 to moist air. As a result, the solar cell device was found to exhibit remarkably improved moisture stability, maintaining a performance of 85% for 14 days of exposure to 85% relative humidity without any encapsulation. We investigated the effects of the PEI introduction on the perovskite solar cell properties and demonstrated for the first time that the strong adhesion of the CH3 NH3 PbI3 /HTM layer results in a perovskite solar cell device that is not only mechanically stable but also exhibits high long-term stability.